Assessment of genetic diversity of some Siberian and Far Eastern species of the genus Spiraea (Rosaceae) by newly developed multiplex panels of nuclear SSR loci - T. A. Poliakova; A. V. Shatokhina; G. N. Bondarenko; D. V. Politov (Вавиловский журнал генетики и селекции)
Taxonomic and population genetic studies of the genus Spiraea (Rosaceae) species require new informative genetic markers. We screened 37 previously published heterologous oligonucleotide primer pairs for nuclear microsatellite loci and selected eight polymorphic and most reproducible of them for PCR multiplexing which substantially increases performance of routine mass genotyping. Three multiplex sets of 3, 3 and 2 loci, respectively, were developed and tested for ability to estimate the parameters of genetic variability and  population  structure in closely related species Spiraea ussuriensis, S. f lexuosa, S. chamaedryfolia representing seven natural populations of the Russian Far East and Siberia. Allele number ranged among loci from twelve (Spth20) to three. Among 41 alleles found, 7 were unique in some species/populations. Analysis of parameters of genetic variability in Spiraea spp. showed similar values of allele number per locus and observed heterozygosity among populations and slightly greater estimates of expected hete rozygosity in the samples of S. f lexuosa (NA = 2.387; HO = 0.387 ± ± 0.052; HE = 0.540 ± 0.055) as compared to S. ussuriensis (NA = = 2.781; HO = 0.385 ± 0.079; HE = 0.453 ± 0.072) and S. chamaedryfolia (NA = 2.875; HO = 0.331 ± 0.071; HE = 0.505 ± 0.069). The observed values of genetic polymorphism parameters indicate the average level of genetic diversity of the studied species typical to previous studies in Spiraea. About 19 % of the observed variability occurred among populations (FST = 0.191) while 81 % of the total genetic variation concentrated within the populations. The loci VS11, VS12, VS2, and VS6 contributed most to the observed differentiation. Nei genetic distances  between populations ranged from 0.049 to 0.585. Genetic differentiation patterns among studied populations based on allele frequencies of nuclear microsatellite loci correspond with their geographical location. Genetic composition of some samples contradicted with their provisional species identification.